PERBANKAN SYARI’AH DI INDONESIA; PELUANG DAN TANTANGANNYA (Pendekatan Analisis SWOT) - Rasiam, Rasiam (Khatulistiwa, 2012)
The will to develop the economy of Sharia is not solely due to the spirit of religion will but there is disclosure of truth and practice of the result of scientific evolution particularly in the field of economics. The main reason is a justice perspective so as to generate ghiroh to articulate in the real world. In fact, the Sharia-based economy has evolved in some countries, even in countries that had previously proposed and implemented the concept of conventional economy with the capitalistic system. Along with these developments, Sharia economics began to appear in Colleges. In a real context, the Sharia economic system has already been practiced in the banking world. In Indonesia, the trigger was Law No. 7/1992 which was later changed to law No. 10/1998.